ARBITRAGE AND INTEREST RATE PARITY: IMPLICATIONS FOR FOREIGN EXCHANGE INVESTORS AND SPECULATORS - Febrianto, M. Nanang; Subagiyo, Rokhmat; Aswad, Muhammad (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2025)
Globalization has an impact on the development of international trade, which can increase market share. In addition, in foreign exchange trading, currency is not just a transaction tool but also a commodity traded in the foreign exchange market. The study aims to analyze arbitrage and interest rate parity on its implications for foreign exchange investors and speculators. Secondary data used in the study were obtained from books, national and international edited journals, news, and working papers conducted by a literature review. It is found that unstable economic conditions, increased inflation, and speculators can increase the volatility of exchange rate imbalances in the foreign exchange market. exchange rate differences can be utilized by arbitrageurs and will naturally move towards efficiency. However, the enactment of purchasing power parity implies indifferent behavior to invest domestically or internationally because the returns obtained are not greater than domestic. In addition to maintaining foreign exchange stability, intervention policies are needed through controlled floating exchange rates, interest rate policies, maintaining liquidity and capital flows carried out by monetary authorities and central banks, as well as reducing import dependence and increasing exports